The Impact of Digital Marketing Exposure on the Consumption Behavior of Generation Z Students: Evidence from an Indonesian Public Junior High School - Kusuma wijaya; La Ode Almana; Fitriyani; Haldi Jofanda (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
This study analyzes the influence of digital marketing exposure on the consumption behavior of Generation Z students at SMP Negeri 31 Padang. Using a quantitative approach, data were collected from 75 purposively selected students through Likert-scale questionnaires. Descriptive analysis reveals that the majority of students experience high levels of digital marketing exposure. Simple linear regression analysis demonstrates a significant positive effect, with a regression coefficient () of 0.711 and a significance value of 0.000. The coefficient of determination () of 0.425 indicates that digital marketing exposure explains 42.5% of the variance in students' consumption behavior. These findings confirm that digital marketing serves as a powerful psychological trigger for impulsive consumption among early adolescents. The study's novelty lies in providing empirical evidence of digital marketing's impact on the "early adolescent" segment in a localized Indonesian context, highlighting their high susceptibility compared to older demographics. The implications suggest an urgent need for digital literacy interventions in schools to mitigate the risk of early-onset consumerist habits driven by pervasive digital stimuli.